Sustainable wine tourism as a diversification strategy: a different approach in a rural cooperative - Almeida, Dora (2023)
In January of 2018, Jos e Miguel Almeida (JMA), leader of the Board of Directors (BD) of Vidigueira Cuba & Alvito (ACVCA) wine cooperative, one of the Portugal’s oldest wine cooperatives, located in the south of the country, on Alentejo region, was preparing the first meeting with the newly elected BD. The purpose of this case study is to help the board of ACVCA to design the strategy for the next four years, taking into consideration some possible options. Should they put all their eggs in one basket? Or, on the contrary, should they diversify and open up different ways? In addition to sustainability in its three pillars (economic, environmental and social), they must consider that cooperators demand guaranteed respective income, “We can’t risk everything”, thought JMA! The BD would have to make decisions not only for the affirmation of the brand but also to its renown and sustainable growth. It was necessary to define a path that did not put at risk the stability achieved, but that allowed new markets to be reached and new challenges embraced. How could it be done? Increasing production capacity or investing in internationalisation, focusing on segmentation through innovation, could be two different ways. Diversification of product or business area was also an option. Wine tourism was one of the options. “Can we do it sustainably and differently?” thought JMA. “We have to push for creativity and take advantage of our strengths, our traditions and customs, our material and immaterial heritage”. Could ACVCA explore its singularities? Could it be done through Amphora wine, [1] produced from its exclusive centuries-old grape varieties? Which was the best way? These questions would have to be discussed with all BD members in the next meeting. Considering the crucial role of cooperatives in developing the regions where they were located, the success of the defined strategy was extremely important for ACVCA and all its stakeholders, including the local community. “Strategic management decisions in a cooperative always have a double objective: on the one hand, to satisfy the interests of the cooperators and, at the same time, to meet the interests of the market and assert its positioning in an increasingly competitive sector”, thought JMA.